The effectiveness and cost effectiveness of a national lay-led self care support programme for patients with long-term conditions: a pragmatic randomised controlled trial. Issue 3 (26th February 2007) - Kennedy, Anne; Reeves, David; Bower, Peter; Lee, Victoria; Middleton, Elizabeth; Richardson, Gerry; Gardner, Caroline; Gately, Claire; Rogers, Anne
Abstract : Objective: Supporting patients' self care could have a major effect on the management of long-term conditions, which has led to worldwide interest in effective self care interventions. In England, self care support is being developed through the "Expert Patients Programme", which provides lay-led generic courses to improve patients' self care skills. However, the clinical and cost effectiveness of such courses remains unclear. Methods: Two-arm pragmatic randomised controlled trial design with waiting list control in community settings in England. 629 patients with a wide range of self-defined long-term conditions were studied. The lay-led self care support group involved 6-weekly sessions to teach self care skills. Primary outcomes were self-efficacy, reported energy and routine health services utilisation at 6 months. A cost-effectiveness analysis was also conducted. Results: Patients receiving immediate course access reported considerably greater self-efficacy and energy at 6-month follow-up, but reported no statistically significant reductions in routine health services utilisation over the same time period. The cost-effectiveness analysis showed that patients receiving immediate course access reported considerably greater health related quality of life, and a small reduction in costs. If a quality adjusted life year was valued at £20 000 (39 191; €30 282), there was a 70% probability that the intervention was cost effective. Conclusions: Lay-led self care support groups are effective in improving self-efficacy and energy levels among patients with long-term conditions, and are likely to be cost effective over 6 months at conventional values of a decision-maker's willingness to pay. They may be a useful addition to current services in the management of long-term conditions.